Analysis of Financial Performance Before and After the Implementation of BLU Financial Management Patterns at Level III Salak Bogor Hospital - Hurriyaturrohman, Hurriyaturrohman; Masyitoh, Siti; Rizqi, Muhammad Nur (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2024)
The research aims (1) to determine the performance of the Salak level III hospital before and after the implementation of the BLU financial management pattern (2) to find out whether there are significant differences before and after the implementation of the BLU financial pattern (3) To find out the obstacles that arise in implementing BLU in level hospitals III Salak Bogor. This research uses comparative descriptive research with a quantitative approach, namely comparing financial performance ratios before and after the implementation of the BLU financial pattern including cash ratio, current ratio, receivables collection period ratio, fixed asset turnover ratio, fixed asset return ratio, return on equity ratio and income ratio. PNBP on operational costs. The results of research on financial performance after BLU experienced a significant increase except for the asset turnover ratio. Innovation is needed to find and develop resources to improve financial performance